2013
DOI: 10.1016/j.aap.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The influence of economic incentives linked to road safety indicators on accidents: The case of toll concessions in Spain

Abstract: The goal of this paper is to evaluate whether the incentives incorporated in toll highway concession contracts in order to encourage private operators to adopt measures to reduce accidents are actually effective at improving safety. To this end, we implemented negative binomial regression models using information about highway characteristics and accident data from toll highway concessions in Spain from 2007 to 2009. Our results show that even though road safety is highly influenced by variables that are not m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
6
9
0
Order By: Relevance
“…As expected, as the RL parameter was positive, this indicates an increase in the number of accidents as this variable increases, which is consistent with the reports by [13,22,23]. Similar behavior indicates the RW variable, i.e., the wider the roadway, the more interaction there is between the vehicles, which increases the probability of collisions; such a result is consistent with [24,25].…”
Section: Determination Of Accident Prone Road Sections and A Hazard Rsupporting
confidence: 80%
See 2 more Smart Citations
“…As expected, as the RL parameter was positive, this indicates an increase in the number of accidents as this variable increases, which is consistent with the reports by [13,22,23]. Similar behavior indicates the RW variable, i.e., the wider the roadway, the more interaction there is between the vehicles, which increases the probability of collisions; such a result is consistent with [24,25].…”
Section: Determination Of Accident Prone Road Sections and A Hazard Rsupporting
confidence: 80%
“…In addition, the statistical significance of the P50 estimator for the accident occurrence model is evident. However, the negative parameter indicates that an increase in the average speed of the study sections will result in a decrease in accidents, which is not a common result, even though it is consistent with the results reported by [22,27]. One of the possible causes of this result is that the SD of the average speed of the road sections is very low, therefore the speed range of those sections is also low.…”
Section: Estimation and Analysis Of The Modelsupporting
confidence: 80%
See 1 more Smart Citation
“…A database was prepared containing the records of accidents that occurred in the urban perimeter of the municipality of Ocaña between the years 2007 and 2013 (up to August), which is suitable for this type of study according to reports of other investigations that calibrate models based on historical data for a shorter time period [12], [14], [20]. At the same time, and based on previous studies [3], we identified 15 road-traffic corridors for Ocaña.…”
Section: Accident Data and Variables Usedmentioning
confidence: 99%
“…Calibration of the accidentfrequency model was based on Poisson and NB regressions, seeing as there are plenty of studies in literature where they have been widely utilized [14]- [20]. Some studies make recommendations on the estimation of the model, as sometimes possible sources of error are evident in the prediction model due to the existence of collinearity between the dependent variables and an incorrect functional form of dependent and independent variables [21], [22].…”
Section: Introductionmentioning
confidence: 99%